RESULTS OF RESEARCH AT THE ARCHAEOLOGICAL COMPLEX SIMONOVKA 11 (AKKANBURLYK) IN 2023 (Journal of history, 2024)
The study of medieval archaeological sites of Northern Kazakhstan is one of the important directions in Kazakhstani science. However, until recently, no full-fledged archaeological work was carried out in the North Kazakhstan region.During the work at the Simonovka-11 complex in 2023, a comprehensive set of scientific research activities was conducted using traditional excavation methods and modern technologies for documentation, collection, and study of materials. Prior to excavation, a field survey of the site was carried out, and a location for the excavation was selected based on the results.A big event was the opening in 2022 of the branch of the Margulan Institute of Archaeology at the M.K. Kozybayev North Kazakhstan University in Petropavlovsk. The following year, a joint archaeological survey was conducted in seven districts of the North Kazakhstan region. This led to the discovery of the Simonovka 11 (Akkanburlyk) complex in the G. Musrepov district, comprising a structure, a cluster of four boulders and large stones, a circular mound, and a kurgan. In the same season, excavations were carried out at the complex. As a result, a flagstone building with a basement was investigated, dated by radiocarbon dating data from the second half of the 19th – early 20th century) and a kurgan of the 11th–14th centuries. The kurgan turned out to be looted, but the grave pit provided rich material – silver earrings, lapis lazuli and paste pendants, paste, jade and carnelian beads and a bone whistle from the arrowhead. Lapis lazuli pendants and carnelian beads are analogous to finds from the burials of the famous Basandai burial mound of the 11th–14th centuries in the Tomsk-Ob interfluve. The bone whistles have a long and interesting history of origin and distribution. Excavations at the Simonovka 11 site highlighted the need for further research in the North Kazakhstan region.
Keywords: Northern Kazakhstan, archaeology, ethnography, construction, the Middle Ages, kurgan, lapis lazuli pendants, whistle.